The Existence of MUI Fatwa No. 1 of 2004 Concerning Islamic Financial Institutions for the Indonesian Muslim Community - Witasari, Aryani; Rondhiyah Dwi Istinah, Siti (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
In order to support and improve the country's economy through Islamic financial institutions, the government through the Indonesian Ulema Council issued MUI Fatwa No. 1 of 2004. The research method used is a normative legal approach method supported by primary data, namely by using unstructured interviews with human resources working in banking institutions. The existence of MUI Fatwa No. 1 of 2004 shows that it is not yet as effective as expected in inviting Indonesian Muslim society to switch to a profit-sharing system and abandon usury. The practice of implementing the sharia system is still hampered by several things, including the service felt by the community in sharia banking institutions is still not satisfactory enough, such as the burden of profit sharing which is still high, the implementation of the sharia system which seems to be the same as conventional banks, the knowledge of human resources about sharia which is still minimal and the explanation of information is lacking.